Pendidikan Islam sebagai agen perubahan sosial: Analisis sosiologis atas peran guru dan moralitas - EL-Muda'afi, Muhammad Tastaftiyan; Khasanah, Nur (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
Islamic education that contributes to building a generation that is intellectually sound and morally upright. In a world of constant social evolution, teachers also use Islamic education to inculcate moral values in their students, such as honesty, empathy, discipline, and civic responsibility. That is to say, teachers are not merely “learned” individuals, but role models who guide students on how to live religiously and apply faith in everyday life. By upholding these values consistently, it fosters good social conduct and facilitates integration into a better society. Islamic education plays a role in mediating between sublime spiritual and moral values on the one hand, and challenging real social situations on the other. The quality of this process depends greatly on the relationship formed between teacher and student. Through content that is relevant and contextual, Islamic education produces generations that are socially conscious, responsible, and capable of acting as agents of social change. This research seeks to explore from a sociological perspective how Islamic education, particularly through the role of teachers in schools, can influence students’ moral character and contribute to broader social transformation.